2014
DOI: 10.1186/1749-799x-9-44
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of midfoot osteotomy combined with adjacent joint sparing internal fixation in treatment of rigid pes cavus deformity

Abstract: BackgroundMidfoot osteotomy has been previously confirmed to be a good method to correct pes cavus. How to fix the osteotomy and which point to choose for the procedure has been a focus for most surgeons. The aim of this study was to analyse the outcomes of a series of patients who had been treated for pes cavus deformity using midfoot osteotomy combined with adjacent joint sparing internal fixation.Materials and methodsBetween 2008 and 2012, 17 patients with a mean age of 16.8 years (12–36 years) were tracked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…It is a sensorimotor orthosis which increased medial ground reaction forces and increase pressure at the heel, midfoot and toes. Sensorimotor orthoses produce changes in kinematic, kinetic and pressure variables in adults with CMT and are re- [29], where high results of these operations were proved, were revealed. However, there should always be cautious in prescribing such a radical treatment [30], also for neuromuscular diseases, in the cases when surgery is not the final treatment, it is also necessary to conduct long-term postoperative facilitation and, in one way or another, training in a new way of life and sports regimen.…”
Section: ) Effectiveness Of Orthotics In Cmtmentioning
confidence: 98%
“…It is a sensorimotor orthosis which increased medial ground reaction forces and increase pressure at the heel, midfoot and toes. Sensorimotor orthoses produce changes in kinematic, kinetic and pressure variables in adults with CMT and are re- [29], where high results of these operations were proved, were revealed. However, there should always be cautious in prescribing such a radical treatment [30], also for neuromuscular diseases, in the cases when surgery is not the final treatment, it is also necessary to conduct long-term postoperative facilitation and, in one way or another, training in a new way of life and sports regimen.…”
Section: ) Effectiveness Of Orthotics In Cmtmentioning
confidence: 98%
“…After 5.4 years of follow-up, the excellent and good rate reached 77%. [22]Zhou et al [23] reported 17 cases of adolescents and young adults (12-36 years old) who underwent cole midfoot osteotomy, including navicular wedge fusion and dice bone closed wedge osteotomy, combined with percutaneous plantar fascial release treatment. In some of our patients, anchors were used to selectively transfer the posterior tibial tendon through the interosseous membrane to the dorsalis pedis; In the case of horseshoe muscle contracture, the Achilles tendon "Z" lengthening is performed.…”
Section: First Metatarsal Osteotomymentioning
confidence: 99%
“…For the calcaneus and first metatarsus, for example (►Fig. 2c), the angle between their longitudinal axes is calculated, as already reported in the literature ("calcaneal-first metatarsal" [C1MA or CA-MT1] 19,20 and the Hibb angle 18,21 ).…”
Section: Current Techniques and Applications At The Orthopaedic Centermentioning
confidence: 99%